The endowment effect: Loss aversion or a buy-sell discrepancy? - Smitizsky, Gal; Liu, Wendy; Gneezy, Uri (Journal of experimental psychology. General, 2021)
In a typical endowment effect experiment, individuals state a higher willingness-to-accept to sell an object than a willingness-to-pay to obtain the object. The leading explanation for the endowment effect is loss aversion for the object. An alternative explanation is based on a buy-sell discrepancy, according to which people price the object in a strategic way. Disentangling these two explanations is the goal of this research. To this end, we introduce a third condition, in which participants receive an object and are asked how much they are willing to pay to keep it (Pay-to-Keep). Comparing the three conditions we find no evidence for loss aversion in the endowment effect setting. We found support for the buy-sell strategy mechanism. Our results have important implications for the understanding of buyer and seller behaviors, subjective value, and elicitation methods. (PsycInfo Database Record (c) 2021 APA, all rights reserved).